Parenting and social‐ecological correlates with children's health behaviours: A latent profile analysis. Issue 10 (1st September 2020) - Fu, Emily; Grimm, Kevin J.; Berkel, Cady; Smith, Justin D.
Summary: Background: Paediatric obesity poses dangers to children's short and long‐term health. Multi‐level ecological models posit how children's health behaviours are influenced by interpersonal relationships. Objectives: To identify profiles of individual and interpersonal health behaviours and parenting skills among caregivers and their children with elevated BMI. Methods: Participants were 240 children (63.7% Latino) ages 5 to 12 years with body mass index ≥85th percentile and their caregivers in a paediatric weight management intervention trial. A latent profile analysis was used to identify profiles among caregiver report of parenting skills; child physical activity, eating behaviours, and food and beverage choices; family mealtime, media and sleep routines; and parent health behaviours, and associations with food and housing insecurity. Results: A three‐class model was chosen based on conceptual interpretation and model fit. Profiles were differentiated by parenting skills, child food choices, child physical activity habits, family mealtime, media, and sleep routines, and parent health behaviours. Food and housing insecurity were associated with class membership while child and caregiver anthropometrics were not. Conclusions: Distinct profiles existed among this low‐income, racially/ethnically diverse sample of children with elevated BMI. Such findings emphasize the importance of assessing individual and interpersonal influences and contextual factors on childhood obesity.